Failed tableland: geomorphological map of the Sarmiento Basin (extra-Andean Patagonia, Argentina) - Jakub Kilnar; Tomáš Pánek; Diego Winocur; Michal Břežný (Journal of Maps)
We present a 1:120,000 landslide-focused geomorphological map of the Sarmiento Basin (Chubut Province, Argentina) and the adjacent landscape. The study area covers about 8000 km2 and can be schematically described as an endorheic basin enclosed by tableland. However, the landscape shows a high diversity of landforms and features. The mapping was mostly conducted manually, based on high-resolution satellite images and a digital elevation model, and supported by field observations. We divided the mapped landforms and features into six categories based on their prevailing origin: structural and volcanic, mass movement, hillslope erosional, fluvial, lacustrine and aeolian. We highlight the abundance of landslides (23% of the study area) in the context of volcanic plateaus and (paleo)lake level evolution. The presented map is unique due to the overall scarcity of detailed geomorphological maps of tablelands worldwide and the insufficient documentation of landslides in the extra-Andean Patagonia.